The Effectiveness of Health Education in Improving Understanding of Prevention of Cerebrovascular Stroke - Fitria M. Radjak; Ismiyati Hi. Yusuf; Sitti Ramlah Anwar (Jurnal Penelitian Perawat Profesional, 2025)
Cerebral Vascular Attack (CVA) or stroke is a serious condition resulting from interrupted blood flow to the brain, potentially leading to brain cell damage or death. This study investigates how health education about cholesterol can enhance community awareness of CVA prevention in Bontoramba, Tamalanrea, Makassar. The purpose of this study was to evaluate the effect of health education related to cholesterol on increasing public awareness in preventing CVA. This study employed a quantitative experimental design using a one-group pre-test and post-test approach with observations. Conducted from July 2 to 8, 2025, it involved 45 community respondents from Bontoramba, selected using purposive sampling technique. Data were analyzed using paired sample t-test and Fisher Exact Test at a 0.05 significance level. The results of the analysis show that there is a significant difference between respondents' knowledge before and after the counseling. The p-value = 0.000 (<0.05) indicates that there is a significant effect of health counseling on cholesterol on increasing public understanding of CVA prevention. The increase in knowledge after the counseling session proves that health education plays an important role in raising public awareness about the risks of high cholesterol, which causes strokes. The information provided broadened the respondents' understanding so that they were able to implement preventive measures more effectively. Health education about cholesterol has been proven to increase public knowledge about CVA prevention in Bontoramba, so it needs to be continuously promoted as a preventive measure to reduce the risk of stroke.